Analisis Asuhan Keperawatan pada Pasien Lansia Hipertensi dengan Perfusi Perifer Menggunakan Intervensi Massage Kaki di Wilayah Kerja Puskesmas Bontosikuyu Kabupaten Kepulauan Selayar - Andi Tenri; Fanny Dewi Sartika; Asriani Bahar; Khumaidi Arief (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2026)
Hypertension is a chronic disease that is common worldwide, typically known as high blood pressure. Hypertension is a chronic condition characterized by increased blood pressure on the arterial walls, often referred to as high blood pressure due to increased systolic blood Pressure above the normal limit of 140 mmHg and diastolic blood pressure above 90 mmHg. This study aims to evaluate the effectiveness of foot massage therapy in reducing blood pressure in elderly hypertensive patients. This study uses a descriptive case study design to thoroughly examine the application and impact of foot massage therapy. The initial assessment results show that the research subject experienced hypertension with a significant increase in blood pressure. After applying foot massage therapy gradually for three days, a decrease in blood pressure was observed, indicating the effectiveness of the intervention. The subject's blood pressure condition showed improvement and was resolved. This study concludes that foot massage therapy is effective in reducing blood pressure in elderly hypertensive patients. These results suggest that foot massage therapy can be a beneficial non- pharmacological intervention in managing hypertension in the elderly.